Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10900-014-9834-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Breast Cancer Screening in Low-Income African Americans in Tennessee

Abstract: This study examined demographic and lifestyle factors that influenced decisions and obstacles to being screened for breast cancer in low-income African Americans in three urban Tennessee cities. As part of the Meharry Community Networks Program (CNP) needs assessment, a 123-item community survey was administered to assess demographic characteristics, health care access and utilization, and screening practices for various cancers in low-income African Americans. For this study, only African American women 40 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 19 publications
2
34
0
2
Order By: Relevance
“…Possible implicating factors can include socioeconomic as well as biological status. 3 In our study, a greater percentage of African Americans were insured through Medicaid, whereas a greater percentage of whites had private health insurance. We did not determined patient socioeconomic status in our study, but these f ndings may imply that socioeconomic status was a factor.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Possible implicating factors can include socioeconomic as well as biological status. 3 In our study, a greater percentage of African Americans were insured through Medicaid, whereas a greater percentage of whites had private health insurance. We did not determined patient socioeconomic status in our study, but these f ndings may imply that socioeconomic status was a factor.…”
Section: Discussionmentioning
confidence: 53%
“…15 Mammography use among African American women seems to correlate with household income. 3,16,17 T is study demonstrated that white women with breast cancer in Central Georgia were more likely to have private insurance than were African American women with breast cancer. In addition, Medicaid rates among African Americans were signif cantly higher than among their white counterparts.…”
Section: Screening Mammographymentioning
confidence: 96%
“…Advantaged segments of the population may be better educated, better insured, and more highly resourced, and this may lead to higher and quicker utilization of mammography, diagnostic screening tests, and cutting-edge cancer treatments. [34][35][36][37][38][39][40] Biologic differences could also be unmasked by improved treatments. For example, it is possible that the development of effective treatments for receptor-positive cancers unmasked inadequacies in our treatment of triplenegative breast cancer, which is more common among black or African American women.…”
Section: Discussionmentioning
confidence: 99%
“…The potentially significant impact that social support can have on breast cancer detection, treatment, and survival has been well described [45][46][47]. Married women are also more likely to participate in breast cancer screening compared to their unmarried counterparts [48][49][50]. J Womens Health Gyn 2016 | Vol 3: 104…”
Section: Discussionmentioning
confidence: 99%